SEX RATIO, GROWTH PATTERN, AND REPRODUCTIVE POTENTIAL OF THE BEARDLESS BARD (ANEMATICHTHYS APOGON) FROM THE TELABANG RIVER IN THE SUBAH VILLAGE TAYAN HILIR SANGGAU RECENCY - sofia yunita; widadi padmarsari soetignya; ahmad mulyadi (Fakultas Pertanian Universitas Tanjungpura, 2019)
ABSTRACT The beardless barb (Anematichthys apogon) is one of the dominant fish species in the Telabang River, Subah Village, Tayan Hilir, Sanggau Regency. However, there is little biological information, one of the important aspects of reproduction to help plan fisheries management. The main objective of this study was to determine some aspects of the reproductive biology, namely sex ratio, growth pattern, and fecundity. Biweekly sampling was conducted by using purposive sampling method from Juli to September 2018. The result showed that significant sex ratio was 2,2 : 1 (male : female). The significant different of sex ratio from the total length structure are fish measuring 60-69, 70-79, 80-89, 100-109, 110-119, and 120-129 mm. The relationship of total length and total weight was showing positive allometric of growth pattern for males (b = 3,44) and the combination of males and females (b = 3,41), meanwhile found the isometric pattern of growth for females (b = 3, 07). The total fecundity was about 430-1.703 eggs and relative fecundity is about 42 to 199,65 eggs/gram total weight of fish. The relationship between total fecundity with length and total weight showed that total fecundity had no relationship to the length and total weight of the beardless bard. iiKeyword : Reproductive Biology, Fecundity, Allometric, Isometric.